Use of Polynomial Mode Shape Function in Free Vibration Analysis of Cantilever Pelton Turbine - Chhantyal, Bikki; Adhikari, Manoj; Chaudhary, Bir Bahadur; Luintel, Mahesh Chandra (Kathford Journal of Engineering and Management, 2024)
In this study, we investigate the use of polynomial mode shape functions in the free vibration analysis of a cantilever Pelton turbine and compare it with the conventional transcendental mode shape function. The mathematical model is developed using the assumed mode method and Lagrange’s equation, incorporating rotational inertia and centrifugal effects. Variable mode shapes and critical frequencies are determined using both polynomial and transcendental functions, and are compared exclusively. The results show that polynomial mode shape functions closely approximate the first mode shape but the deviation increases in higher modes, with a critical frequency deviation of 2.23% in the first mode and 14.58% in the second mode and 20.53% in the third mode. These findings suggest that while the polynomial mode shape functions offer computational simplicity, their accuracy decreases in complex rotor-dynamic systems. We can use polynomial mode shape function is case of simple dynamics and problems in which higher modes are negligible. Being the Cantilever Pelton Turbine complex, presently designed mathematical model and its outcomes are fully vowed to explain its vibrational consequences for first mode. The authors believe that the findings obtained through this theoretical work are applicable not only to Cantilever Pelton turbines but also to other rotor-dynamic systems with similar boundary conditions, such as turbine blades, flexible shafts, and cantilevered rotor structures in hydro and wind energy applications.